Licensing of Forest Pesticide Applicators in Florida - Frederick M. Fishel (EDIS)
PI-130, a 4-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply pesticides to forest sites in Florida, as regulated by the Florida Pesticide Law (Chapter 487), and administered by the Florida Department of Consumer Services. Published by the UF Pesticide Information Office, July 2006.